Potential bias of fungal 18S rDNA and internal transcribed spacer polymerase chain reaction primers for estimating fungal biodiversity in soil - Anderson, Ian C.; Campbell, Colin D.; Prosser, James I. (Environmental microbiology, 2003)
Summary Four fungal 18S rDNA and internal transcribed spacer (ITS) polymerase chain reaction (PCR) primer pairs were tested for their specificity towards target fungal DNA in soil DNA extracts, and their ability to assess the diversity of fungal communities in a natural grassland soil was compared. Amplified PCR products were cloned, and ≈ 50 clones from each library were sequenced. Phylogenetic analysis and database searches indicated that each of the sequenced cloned DNA fragments was of fungal origin for each primer pair, with the exception of the sequences generated using the 18S rDNA primers nu‐SSU‐0817 and nu‐SSU‐1196, where 35 of the 50 sequenced clones represented soil invertebrates. Although some of the primers have previously been suggested to be biased towards certain fungal taxonomic groups, the ratio of sequences representing each of the four main fungal phyla, Ascomycota, Basidiomycota, Chytridiomycota and Zygomycota, was similar for each of the primer pairs, suggesting that primer bias may be less significant than previously thought. Collector's curves were plotted to estimate the coverage obtained for each of the clone libraries after clustering the sequences into operational taxonomic units at a level of 99% sequence similarity. The curves indicated that good coverage of diversity was achieved, with the exception of the clone library constructed using primers nu‐SSU‐0817 and nu‐SSU‐1196, on account of the high number of non‐fungal sequences obtained. The work demonstrates the usefulness of 18S rDNA and ITS PCR primers for assessing fungal diversity in environmental samples, and it also highlights some potential limitations of the approach with respect to PCR primer specificity and bias.